An approach to handle sudden load changes on static voltage stability analysis - Colombari, Luan Filipe dos Santos (2017)
In the context of static Voltage Stability Assessment (VSA), as the power system load grows, bus voltages tend to drop. This reduction may lead to generator or load disconnections caused by undervoltage protection schemes. These events comprise sudden parametric variations that affect the equilibrium diagram and the Voltage Stability Margin (VSM) of power systems. Practical examples of such sudden load changes are caused by the mandatory disconnection of Distributed Generation (DG) units and Undervoltage Load Shedding (ULS). There are no thorough studies in the literature concerning these load parametric variations and the discontinuities that they cause in power system equilibria. This dissertation describes a predictor/corrector scheme specifically designed to handle these discontinuities, so it is possible to evaluate their effect on the VSM of power systems. This method successively calculates the load discontinuities that exist in the equilibrium locus of the system under analysis. It results in the sequence of sudden load variations that happens and their overall impact on the system. When applied to quantify the effect of DG mandatory disconnections and ULS, the proposed predictor/corrector scheme yielded better results than the traditional Continuation Power Flow (CPFLOW), which experienced convergence problems caused by the discontinuities under analysis. However, due to its design, the applicability of the proposed method should be restricted to power systems that go through several successive sudden load changes. In this sense, it should not be regarded as a replacement for the CPFLOW, but rather as a technique that could award this traditional VSA tool with new features to enhance its performance.